Journal club: Why, what, and how? - M S Archana (SRM Journal of Research in Dental Sciences, 2012)
As the body of medical education continues to expand, physicians must develop the necessary skills to keep up with the vast amount of information available. The journal club provides a forum to allow residents to remain updated with the literature while also teaching them the methods to evaluate it critically. The articles are evaluated as to their quality and also whether and how the findings can be applied to practice. Recently, journal clubs have been designed to teach critical appraisal skills to physicians-in-training. This powerful educational tool has played an active role in medical education for over a century. Although this tool has been incorporated in the postgraduate curriculum, there still remains a lack of understanding of the concept and importance of journals. This paper provides a comprehensive review about what a journal article discussion is and how to evaluate a journal club.